2008
DOI: 10.5713/ajas.2008.70597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea Probiotics on the Growth Performance, Meat Quality and Immune Response in Finishing Pigs

Abstract: The objective of this study was to determine the effects of green tea probiotics on growth performance, meat quality and immune response in finishing pigs, and to assess the possibility of substituting green tea probiotics for antibiotics in diets of finishing pigs. This green tea probiotics is made by mixing green tea powder and excipients (defatted rice bran and wheat bran) and fermenting the mixture with beneficial bacteria. A total of 90 crossbreed "Landrace×Yorkshire" finishing pigs with an average body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The definition of microbial feed supplements, Direct-Fed Microbials (DFM), or probiotics as they traditionally have been called is very broad and may include specific and nonspecific yeast, fungi, bacteria, cell fragments and filtrates (Knowlton et al, 2002). The term "probiotic" has been defined as a live microbial feed supplement, which beneficially affects the host animal by improving its intestinal microbial balance (Fuller, 1989;Ko and Yang, 2008). Also, in feed regulation, probiotics were included in the group of microbial feed supplements for stabilizing the microbial communities of the animal's digestive tract and play an important role in animal's protection against harmful microorganisms and strengthen the host's immune system (Salem et al, 2000).…”
Section: Microbial Feed Supplements Characterization and Mode Of Actionmentioning
confidence: 99%
“…The definition of microbial feed supplements, Direct-Fed Microbials (DFM), or probiotics as they traditionally have been called is very broad and may include specific and nonspecific yeast, fungi, bacteria, cell fragments and filtrates (Knowlton et al, 2002). The term "probiotic" has been defined as a live microbial feed supplement, which beneficially affects the host animal by improving its intestinal microbial balance (Fuller, 1989;Ko and Yang, 2008). Also, in feed regulation, probiotics were included in the group of microbial feed supplements for stabilizing the microbial communities of the animal's digestive tract and play an important role in animal's protection against harmful microorganisms and strengthen the host's immune system (Salem et al, 2000).…”
Section: Microbial Feed Supplements Characterization and Mode Of Actionmentioning
confidence: 99%
“…Lymphocyte proliferation test following Concanavalin A (Con A) and lipopolysaccharide (LPS) stimulation showed better lymphoproliferation in green tea-and probiotic-fed pig (Ko & Yang, 2008). Lymphocyte proliferation test following Concanavalin A (Con A) and lipopolysaccharide (LPS) stimulation showed better lymphoproliferation in green tea-and probiotic-fed pig (Ko & Yang, 2008).…”
Section: Piggerymentioning
confidence: 99%
“…The addition of GTB and green tea with probiotics (GT + P) which include Bifidobacterium long, B. infants, B. breve and Lactobacillus helveticus, L. plantarum, L. cases and L. rhamnosu reduced TBARS value. Lymphocyte proliferation test following Concanavalin A (Con A) and lipopolysaccharide (LPS) stimulation showed better lymphoproliferation in green tea-and probiotic-fed pig (Ko & Yang, 2008). Chevon patties treated with 2% GTE were tested for physicochemical and organoleptic qualities, and the results revealed that the pH and the TBA values were significantly lowered with a reduced viral load (Nath, Kumar, Praveen, & Ganguly, 2016).…”
Section: Piggerymentioning
confidence: 99%
“…The desired effect is improved weight gain and feed efficiency via improved gut digestion and reduced pathogenic organism loads. Ko and Yang (2008) found that finishing pigs receiving probiotics in their feed showed equal or superior daily gain, intake, and feed efficiency as pigs fed antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Suga et al (2003) isolated an antioxidative phyllostadimier from Phyllostachys edulis, a common bamboo species. The combination of medicinal plants with probiotics has shown the potential to improve many aspects of broilers (Sarker et al, 2010a(Sarker et al, , 2010b(Sarker et al, , 2010c, pigs (Ko and Yang, 2008) and calves (Sarker et al, 2010e). To the best of our knowledge, there were limited researches has been conducted on the combination of bamboo vinegar and probiotics on the growth performance, fecal microbiology and fecal odorous gas emissions in finishing pigs.…”
Section: Introductionmentioning
confidence: 99%